Upaya Peningkatan Pemahaman Konsep Berhitung Melalui Montessori Di KB Merpati - Retno Ayu Sita Devi; Ujang Maulana Yusup (CV. ITTC INDONESIA, 2025)
This study aims to improve early childhood understanding of counting concepts through the Montessori method at KB Merpati. The research used a Classroom Action Research method conducted in two cycles. The subjects were 17 children from group B. Data collection was carried out using observation sheets, and the data were analyzed using descriptive quantitative techniques. The results showed that the Montessori method, through activities such as grouping objects and number-based board games (e.g., snake and ladder), could enhance children's understanding of counting. The average achievement increased from 30.9% in the pre-cycle to 61.75% in cycle I and 85.3% in cycle II. In conclusion, the Montessori method is effective in developing early childhood counting skills through a concrete, enjoyable, and developmentally appropriate approach.